Spectral Characters: Genre and Materiality on the Modern Stage, Sarah Balkin (2019). Issue 1 (1st June 2021) - Schweitzer, Marlis
Review of: Spectral Characters: Genre and Materiality on the Modern Stage, Sarah Balkin (2019)Ann Arbor, MI: University of Michigan Press, 198 pp., ISBN 978-0-47213-148-8, h/bk, $65